The nematicidal effect of cysteine proteinases on the root knot nematode Meloidogne incognita - Gorny, Samuel Victor (2013)
Despite current control measures, plant parasitic nematodes are estimated to be responsible for > $100 billion of damage to worldwide crop production per annum. Current nematicides are highly toxic, and due to health and environmental safety concerns, many are being withdrawn from the market under directive 914/414/EEC. Alternative control strategies are urgently required. The cysteine proteinases papain, actinidain and recombinant endoproteinase B isoform 2 (R.EP-B2) have been demonstrated to affect the mobility of M. incognita J2s; 50.7 μM R.EP-B2, 101.7 μM papain and 200.3 μM actinidain immobilised 50% of the M. incognita population. Papain has also been demonstrated to affect the infection of plants by M. incognita, 5 μM papain reduced the attraction to and invasion of A. thaliana by 41.2 + 25.6% and 80.4 + 10.5% respectively. M. incognita J2s showed extensive damage to and removal of the cuticle when treated with 100 μM papain. MALDI-TOF analysis identified a number of M. incognita proteins affected by the papain treatment; of particular interest were a cuticle preprocollagen and a rhodopsin-like GPCR chemoreceptor. Proteins of these types are essential for movement and host location, disrupting their function helps to explain the loss of mobility and reduction in A. thaliana infection observed in the bioassays. Finally transgenic A. thaliana was generated with the barley cysteine proteinase endoproteinase B isoform two under the control of the root cap specific MDK4-20. The preliminary testing of these plants showed a reduction in root invasion similar to that obtained with papain.